Popular culture in Amapá webjournalism: the representations of the Festa de São Tiago (Revista Internacional de Folkcomunicação, 2018)
From the theoretical discussion related to the concepts of Folkcommunication, the present article intends to describe how the actors involved with the Festa de São Tiago, in Amapá, are represented in the local webjournalism. The tradition of celebrating the feast was brought from Africa to the village of Mazagão Velho in the eighteenth century, keeping in the temporal space by oral narratives. In order to make the observation, the work used the methodological route based on the categorization of news sources – specialist, reference, testimonial, institutional, notable, corporate, official and popular – in the G1 Amapá and SelesNafes.com sites, during July 2017. However, although the rituals and the history of the festival are marked by the intense presence of popular culture, there were predominant official sources in the survey of 20 verified publications. Folkcommunication; Festa de São Tiago; Webjournalism.